Determinants of immunization coverage in Yogyakarta Province - Syarifah Hanum, Syarifah Hanum (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Children and infant immunization are often viewed as the symbol of preventive medicine and health service. Furthermore, immunization coverage is often used as an indicator of health service achievement. Recognizing the determinants associated with infant and children immunization status is one of the efforts to increase immunization coverage.Objectives: To know the immunization coverage in Yogyakarta province and determinants associated with coverage and age on immunization.Materials and methods: This is a cross-sectional study on children 12-23 months of age living in Yogyakarta municipality and other four districts in Yogyakarta province. Subjects were selected using proportional probability multistage cluster random sampling from 30 clusters each representing rural and municipality as urban area.Results: The coverage in municipality as well as in urban areas exceed 90%. The coverge is too high to allow analysis on unimmunized children. We found no statistically significant difference of coverage between rural educational level and though there was a significant difference in parental educational level and occupation distance to nearest health center and age on immunization (p>0.05). There is a statistically significant difference between age on BCG and hepatitis B immunization with place of immunization (p<0.05).Conclusion: Immunization coverage in Yogyakarta province based on survey exceeded 90%. Determinant associated with age on immunization was place of immunization.Key words: immunization coverage - determinant - age on immunization.Â